2008
DOI: 10.1161/hypertensionaha.108.189141
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Hypertension: Diagnosis, Evaluation, and Treatment

Abstract: Abstract-Resistant hypertension is a common clinical problem faced by both primary care clinicians and specialists. While the exact prevalence of resistant hypertension is unknown, clinical trials suggest that it is not rare, involving perhaps 20% to 30% of study participants. As older age and obesity are 2 of the strongest risk factors for uncontrolled hypertension, the incidence of resistant hypertension will likely increase as the population becomes more elderly and heavier. The prognosis of resistant hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
773
5
23

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,365 publications
(839 citation statements)
references
References 144 publications
20
773
5
23
Order By: Relevance
“…Among several factors that may increase the risk of stroke, hypertension is the single most important one 2. Uncontrolled blood pressure (BP) would lead to atherosclerosis and, in turn, harden and weaken the vessels in the brain, heart, and limbs, causing end‐organ damage 3. However, the occurrence of stroke may directly lead to an acute increase in BP 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…Among several factors that may increase the risk of stroke, hypertension is the single most important one 2. Uncontrolled blood pressure (BP) would lead to atherosclerosis and, in turn, harden and weaken the vessels in the brain, heart, and limbs, causing end‐organ damage 3. However, the occurrence of stroke may directly lead to an acute increase in BP 4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…Resistant hypertension (RH) is defined as the persistence of high blood pressure (BP) ≥140 mm Hg of systolic BP or ≥90 mm Hg of diastolic BP, despite a therapeutic plan with 3 or more antihypertensive drugs, at the full tolerated doses, 1 of them diuretic, in subjects in whom secondary hypertension has been ruled out, as well as poor adherence to antihypertensive therapy 1. Several studies have observed a prevalence of around 12% to 14% of treated hypertensives 2, 3.…”
mentioning
confidence: 99%
“…6 By these terms, resistant hypertension includes patients at goal BP using 4 or more antihypertensive agents. Implicit in this definition is the exclusion of causes of pseudoresistant hypertension, including white-coat hypertension, medication nonadherence, and improper BP measurement technique.…”
Section: Definition Of Resistant Hypertensionmentioning
confidence: 99%
“…To effectively exclude causes of pseudoresistant hypertension, current guidelines recommend obtaining either home BPs or, if available, ambulatory BPs. 6,7 Furthermore, patient compliance with antihypertensive therapy should be assessed by medication reconciliation and questioning family members. 7 Definition of aTRH aTRH has been coined to comprise patients meeting the AHA definition of resistant hypertension in whom causes for pseudoresistance have not been thoroughly investigated.…”
Section: Definition Of Resistant Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation